Chalcogen-Based Aerogels As Sorbents for Radionuclide Remediation - Riley, Brian J; Chun, Jaehun; Um, Wooyong; Lepry, William C; Matyas, Josef; Olszta, Matthew J; Li, Xiaohong; Polychronopoulou, Kyriaki; Kanatzidis, Mercouri G (Environmental science & technology, 2013)
The efficient capture of radionuclides with long half-lives such as technetium-99 (99Tc), uranium-238 (238U), and iodine-129 (129I) is pivotal to prevent their transport into groundwater and/or release into the atmosphere. While different sorbents have been considered for capturing each of them, in the current work, nanostructured chalcogen-based aerogels called chalcogels are shown to be very effective at capturing ionic forms of 99Tc and 238U, as well as nonradioactive gaseous iodine (i.e., a surrogate for 129I2), irrespective of the sorbent polarity. The chalcogel chemistries studied were Co0.7Bi0.3MoS4, Co0.7Cr0.3MoS4, Co0.5Ni0.5MoS4, PtGe2S5, and Sn2S3. The PtGe2S5 sorbent performed the best overall with capture efficiencies of 98.0% and 99.4% for 99Tc and 238U, respectively, and >99.0% for I2(g) over the duration of the experiment. The capture efficiencies for 99Tc and 238U varied between the different sorbents, ranging from 57.3–98.0% and 68.1–99.4%, respectively. All chalcogels showed >99.0% capture efficiency for iodine over the test duration. This versatile nature of chalcogels can provide an attractive option for the environmental remediation of the radionuclides associated with legacy wastes from nuclear weapons production as well as wastes generated during nuclear power production or nuclear fuel reprocessing.